New data and synthesis of ΔR estimates from the northern Pacific Ocean. (July 2022) - Khasanov, Bulat F.; Fitzhugh, Ben; Nakamura, Toshio; Okuno, Mitsuru; Hatfield, Virginia; Krylovich, Olga A.; Vasyukov, Dmitry; West, Dixie L.; Zendler, Ekaterina; Savinetsky, Arkady B.
Abstract: We present new data on regional correction factor (ΔR) conducted for Chukotka, the Commander Islands, and the western Aleutian Islands and summarize data previously published for the other parts of the region. Paired radiocarbon dates of coeval marine and terrestrial materials from the archaeological site Kaniskak were obtained in Chukotka, and one such pair was analyzed from Shemya Island (western Aleutians). Three samples of sea otter ( Enhydra lutris ) bones of known collection date were used for the Commander Islands. In conjunction with previously published data, the new results showed that ΔR estimates conducted for the five regions of the northern Pacific do not differ statistically. ΔR assessments combined for archaeological sites resulted in probability density curves of the same shape as that of marine organisms. Comparison of ΔR estimates made with various species of marine animals showed that sea otters and small fishes residing within coastal waters throughout their life histories are better suited for ΔR measurements than migrating seals, on the one hand, and the shells of sedentary organisms, on the other. The study provides additional support to the hypothesis that the northern Pacific is characterized by the same reservoir offset, which we estimate as 525 ± 75 yr.